MENUMBUH-KEMBANGKAN WAWASAN MASYARAKAT TENTANG DINAMIKA PENYAKIT DIABETES MELLITUS MELALUI MEDIA FILM - Y.G. Harto Pramono; Inge Wattimena; Nurlaila Effendy; Michael Seno Rahardanto; Finsensius Yuli Purnama (Widya Mandala Surabaya Catholic University, 2017)
This paper describes the process and the result of educational film media development research aimed to develop the understandings of the society at Kecamatan Tambaksari, Surabaya about the dynamics of Diabetes Mellitus disease. To produce an optimum and pedagogically interesting film media, this media was designed and developed based on the film educational media concepts and its effective principles. Besides, the media was developed based on the needs assessment and the evaluation by experts and a series of tryouts by target users, and revised in stages based on the input and the result of the evaluation. After it had been validated to fit with the expected standard, the quasi experiment was conducted to find out the influence of the media on the learners’ knowledge of Diabetes Mellitus disease. The research design used was the matching only pretest-post test control group design with 40 participants for each group. The data was calculated with the t-Test. There search finding shows that the film media as an educational media has a significant influence on the increase of the society’s knowledge of Diabetes Mellitus disease.